Literary Activity and Ecclesiastical Authority in Medieval Iceland: The Old Norse Reception of St Ambrose of Milan and his Exemplary Role in Bishops’ Sagas - Salmoiraghi, Davide (University of Cambridge, 2023)
This thesis investigates the literary and socio-political impact of the Church’s struggle for *libertas ecclesiae* in the medieval Icelandic Church. I argue that hagiography –in the form of Saints’ sagas– constituted an instrument to promote Gregorian ideals of ecclesiastical independence against secular chieftains from the late twelfth century to the early fourteenth century. As a case study, I focus on the reception of St Ambrose of Milan (374–97), a fundamental theologian in Western Christianity and a skilful diplomat who promoted the superiority of the Late Antique Church over secular interference while simultaneously securing for the Church the support of the Roman Empire. I argue that *Ambrósíuss saga biskups* constituted a source of legitimation in the composition of the sagas of those bishops who successfully fought to free the Icelandic Church from secular control during the *staðamál*, the struggle between clergy and laity for the control over church properties. To evaluate the importance of a seemingly distant saint in the history of the medieval Icelandic Church, I approach the question from an interdisciplinary perspective. Chapter One deals with the presence and cult of St Ambrose in medieval Iceland, from the late twelfth century until the Reformation. Contrary to what has been concluded by previous scholars, evidence from church dedications and ecclesiastical documents demonstrates that devotion to the saint did not falter, and that mentions of Ambrose in secular sagas and historical records suggest that the Icelanders were not unfamiliar with his figure and his importance in the history of the Church. Chapter Two provides background information on the manuscript tradition and narrative structure of *Ambrósíuss saga*. Central to the analysis is the additional material that differentiates *Ambrósíuss saga* from its base text, Paulinus’ *Vita Ambrosii* (BHL 377). I argue that inclusion of this material was meant to delineate a precedent of episcopal authority that could be offered to the Icelandic ...